PSXVI-27 Using tannin to mitigate tall fescue toxicosis. (8th October 2021) - Grote, Ally J; Morgan, Allison; Coffey, Ken; Nieman, Christine; Philipp, Dirk; Kegley, Beth B
Abstract: Fescue toxicosis has a negative impact on livestock production. Tannins could bind to tall fescue toxins rendering them ineffective. The objective was to improve health and well-being of sheep offered tall fescue infected with the endophytic fungus (Neotyphodium coenophialum) by binding toxins in the rumen with condensed tannins. Non-pregnant, non-lactating ewes (n=20; 57±1.3 kg initial BW) were housed in individual 1×1.5-m pens with grate flooring and were offered ad libitum access to either non-toxic novel-endophyte infected tall fescue haylage (NE), or toxic endophyte infected tall fescue haylage with no condensed tannin (E0), or condensed tannin at 10 (E10), or 30 g/kg haylage DM (E30). Additionally, ewes received 4 g/kg BW liquid molasses, which served as the carrier for the condensed tannins in the E10 and E30 treatments. The study consisted of 2, 21-d periods with a 30-d wash out between periods. In each period, a 14-d adaption was followed by 7 d of total fecal and urine collection. Temperature was maintained at 27 to 29 °C. Dry matter and OM intake (g/kg BW; DMI and OMI, respectively) were not affected (P ≥ 0.15) by treatment, but DM and OM digestibility were greater (P < 0.05) from NE vs E30. Digestibility of NDF was greater (P < 0.05) from NE vs E0, E10, and E30. Digestible DMI was greater (P < 0.05) from NE and E0 vs E30, and digestible OMI was greater (P < 0.05) from NE vs E30. Apparent N absorbed (g/kg N intake) was greater (P < 0.05) by lambs offered E0 and E10 compared with E30. Nitrogen retained (g/kg N intake and N absorbed) did not differ (P≥0.29). Therefore, overall impacts of ensiled toxic fescue on lambs were inconsistent and the impact of adding condensed tannins at 30 g/kg DM was negative on most of the DM and OM digestibility measurements.